2007
DOI: 10.1007/s10563-007-9017-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of nickel-mesoporous materials and their application to the hydrodechlorination of chlorinated organic compounds

Abstract: Mesoporous materials have attracted considerable attention for use as a catalyst or a catalyst support due to their remarkable textural properties such as high surface area and large pore volume with a narrow pore size distribution. Many efforts have been made to design mesoporous materials for use in heterogeneous catalyst systems. Recent progress and results regarding the preparation of nickel-mesoporous materials and their application to the hydrodechlorination of chlorinated organic compounds were discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…From Table 1 it is observed that relatively high mesoporous volumes around 0.6 and 0.5cm 3 g -1 were obtained from the DR calculation method for the 20 and 40wt.% Ni loadings respectively; it has been reported that mesoporous materials tend to have ordered pore structures with narrow pore size distribution, high surface area and large pore volumes [41].…”
Section: Bet Analysis Of Fresh Catalystsmentioning
confidence: 97%
“…From Table 1 it is observed that relatively high mesoporous volumes around 0.6 and 0.5cm 3 g -1 were obtained from the DR calculation method for the 20 and 40wt.% Ni loadings respectively; it has been reported that mesoporous materials tend to have ordered pore structures with narrow pore size distribution, high surface area and large pore volumes [41].…”
Section: Bet Analysis Of Fresh Catalystsmentioning
confidence: 97%
“…One relevant parameter from the BET analysis is the total surface area as it is generally related to the accessibility of active sites, hence it is associated with the catalytic activity [37]. From the results obtained it was observed that for the BHPG catalysts, the activity towards hydrogen production followed the same order as the surface area; the highest surface area of 440 m 2 g -1 resulted in the highest hydrogen production 19 mmol H 2 g -1 RDF .…”
Section: Catalytic Activity Of the Ni/sio 2 Catalysts During Pyrolysimentioning
confidence: 97%
“…A Varian 3380 GC with a 80-100 mesh HayeSep column and N 2 carrier gas and flame ionisation detector was used to analyse hydrocarbons (C 1 -C 4 ). to the catalytic activity of the catalyst, in which high surface area typically improves the activity of the catalyst [16,17]. Addition of the Cu, Mg and Co promoters to the Ni-Al catalyst reduced the surface area of the catalysts.…”
Section: Experimental Systemmentioning
confidence: 99%